Evtrična rjava tla – najboljša kmetijska tla v Sloveniji - Grčman, Helena (Geodetski vestnik, 2023)
This paper presents the main characteristics of Eutric Cambisols, their productivity potential expressed as land-rating, and their spatial distribution in Slovenia. Differences in soil properties were evaluated among the six predominant groups of Eutric Cambisols; classification was based on the parent material. In addition to individual characteristics affecting soil quality (texture, soil depth, amount of plant available water, pH, base saturation, cation exchange capacity), a comparison of land-rating values between the groups was also performed. We analysed 200 profiles excavated as part of the Slovenian Soil Mapping or other soil surveys conducted by the Center for Soil and Environmental Sciences, Biotechnical Faculty, University of Ljubljana. Our results show that Eutric Cambisols cover 15.5% of the area of Slovenia. Most Eutric Cambisols are on flysch (19.3%, 600 km2), followed by Eutric Cambisols on marl (12.7%, 398 km2). Eutric Cambisols on sandy gravel alluvial sediments, an important soil for crop production, cover 295 km2 (9.4%). They have a favourable loamy texture and optimal pH. The flat terrain also contributes to this soil’s highest average weighted land-rating value (70 points). The average weighted land-rating value of all Eutric Cambisols is higher than the average weighted land-rating value of all agricultural and forest land in Slovenia, which is 36 points; this must be considered in spatial planning, as this type of land has a small share and above all, it must be protected from various degradations.
Keywords: boniteta; Eutric Cambisols; evtrična rjava tla; kakovost tal; land-rating value; pedologija; Slovenia; Slovenija; soil quality